"It Depends on the Outcome": Prisoners, Grievances, and Perceptions of Justice. Issue 1 (15th January 2018) - Jenness, Valerie; Calavita, Kitty
Abstract : Social scientists have long investigated the social, cultural, and psychological forces that shape perceptions of fairness. A vast literature on procedural justice advances a central finding: the process by which a dispute is played out is central to people's perceptions of fairness and their satisfaction with dispute outcomes. There is, however, one glaring gap in the literature. In this era of mass incarceration, studies of how the incarcerated weigh procedural justice versus substantive justice are rare. This article addresses this gap by drawing on unique quantitative and qualitative data, including face‐to‐face interviews with a random sample of men incarcerated in three California prisons and official data provided by the California Department of Corrections and Rehabilitation (CDCR). Our mixed‐methods analysis reveals that these prisoners privilege the actual outcomes of disputes as their barometer of justice. We argue that the dominance of substantive outcomes in these men's perceptions of fairness and in their dispute satisfaction is grounded in, among other things, the high stakes of the prison context, an argument that is confirmed by our data. These findings do not refute the importance of procedural justice, but show the power of institutional context to structure perceptions of and responses to fairness, one of the most fundamental principles of social life.